Stress Induced Acral Lick Dermatitis in a Domestic Rabbit: A Case Report - Mukesh Srivastava; Anil Ahuja; S. Kachhawaha; N. K Singh; Ankita Sharma; J. P. Kachhawa (Case Reports in Veterinary Medicine)
This case report describes acral lick dermatitis in a six-month-old domestic rabbit, which presented with the complaint of excessive licking of the carpus of left forelimb. Clinical examination showed a single well demarcated, oval, alopecic, ulcerated lesion with peripheral hyperpigmentation and thickening at the carpus of left forelimb. Rabbit was successfully managed with oral fluoxetine and topical application of ointment containing fluocinolone acetonide in 0.025% concentration along with intralesional injection of hydrocortisone of 0.15 mL diluted in normal saline at two sites of a lesion at interval of one week. In addition to medical therapy, hard plastic cat ball, some baby toys, and gnawing sticks were kept with rabbit as a method of environmental enrichment with the purpose of mental stimulation.